Implementasi Dan Tingkat Kepatuhan Terhadap Ketentuan Syari’ah Atas Pembiayaan Murabahah Pada Bank BNI Syari’ah - Sofyan Halim; Torik Langlang Buana (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2020)
In sharia Islam has been arranged in such a way as to do muamalah, on muamalah fiqih has set the terms and conditions in the practice of buying and selling, doing the debts, doing the practice of cooperation in doing business, and many other things. One type of akad in fiqh mu'amalah which justified by Allah SWT is akad buying and selling, namely the hadith which states Ayat Al-Qur'an and al Hadist mentioned above is the legal basis by Shari'ah to do mu'amalah selling buy, be it buying and selling in cash or tough. Akad / Contract of sale and purchase is strong in Islamic shari'ah called Murabahah akad. Murabahah is the sale of goods at the cost of goods acquisition with additional benefits agreed between the seller and the buyer of the goods. Murabaha Akad is one of Sharia bank financing products in conducting syariah banking operations referring to Law no. The Bank's syyar'iah base refers to the Fatwa of the National Shari'ah Council MUI Number 04 / DSN-MUI / IV / 2000 dated April 1, 2000, concerning Murabaha, thus the provisions of legislation on the banking of sharia ' ah and Fatwa DSN MUI become the legal basis of syar'i over the operational of Shari'ah bank as a whole. The purpose of the research is the desire of the researcher to ensure the sale and purchase transaction of murabahah by Bank BNI Syariah has been in accordance with the rules of fiqh mu'amalah and sharia Islam. Based on the Hadith and Fatwa DSN MUI is the Murabahah Akad Financing Guidelines which become the guidelines for the implementation of Murabaha contract financing in PT Bank BNI Syari'ah then the Bank has fulfilled the asset ownership of Murabaha which became one of the terms sharia in Murabaha contract. The Guidelines states that BNI Syariah Bank purchases goods first, then sells it to customers by taking margin/profit. So the Bank must first have the goods before the occurrence of Murabaha agreement with the customer, so there must be proof of ordering/purchasing of goods. Therefore, the Murabaha contract financing by PT Bank Syariah has fulfilled the requirement of Murabaha asset ownership in financing the Murabaha contract to the public. In addition, in PT Bank BNI Syari'ah one of the products offered to the community of residential area development developed by the bank with Murabaha contract financing, then with the scheme, the condition of asset ownership in accordance with the above-mentioned hadith has been fulfilled in full because the ownership before done Murabaha contract is owned by the bank.